2019
DOI: 10.1101/lm.048439.118
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and immunohistochemical characterization of rapid reconditioning following extinction of contextual fear

Abstract: A fundamental property of extinction is that the behavior that is suppressed during extinction can be unmasked through a number of postextinction procedures. Of the commonly studied unmasking procedures (spontaneous recovery, reinstatement, contextual renewal, and rapid reacquisition), rapid reacquisition is the only approach that allows a direct comparison between the impact of a conditioning trial before or after extinction. Thus, it provides an opportunity to evaluate the ways in which extinction changes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 121 publications
(139 reference statements)
1
5
1
Order By: Relevance
“…This ambiguity idea is also consistent with our findings in Experiment 2 that inactivating the BNST impaired initial acquisition of contextual fear with a long session and temporally unpredictable shock. We have previously found that the adBNST is engaged by weak contextual fear using an immediate early gene readout (Williams et al, 2019), but we saw no reliable effect on conditioning in Experiment 1 with a brief context exposure paired with a single US. In some ways, this finding is similar to that reported by Hammack et al (2015), who found that conditioning induced by a single shock after a brief (1 min), but not long (10 min) context exposure, was unaffected by BNST lesions.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…This ambiguity idea is also consistent with our findings in Experiment 2 that inactivating the BNST impaired initial acquisition of contextual fear with a long session and temporally unpredictable shock. We have previously found that the adBNST is engaged by weak contextual fear using an immediate early gene readout (Williams et al, 2019), but we saw no reliable effect on conditioning in Experiment 1 with a brief context exposure paired with a single US. In some ways, this finding is similar to that reported by Hammack et al (2015), who found that conditioning induced by a single shock after a brief (1 min), but not long (10 min) context exposure, was unaffected by BNST lesions.…”
Section: Discussioncontrasting
confidence: 69%
“…Although it is difficult to compare between experiments, it is notable that the postextinction reconditioning effect that we saw in Experiment 1 was large, but the effect that we saw in Experiment 2 was relatively small. In Experiment 1, and in our previous work with rats (Williams et al, 2019), we used a strong acquisition protocol that consisted of 2 days of conditioning. In Experiment 2, because our goal was to evaluate BNST involvement in a single session of conditioning, we only used one day of conditioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current results extend these findings and show that NMDA receptors in the BNST are necessary for both backward fear conditioning to a discrete CS, as well contextual conditioning. These findings are also supported by recent work that observed deficits in contextual fear learning (as well in its reconditioning) after pharmacological inactivation of the BNST (Williams and Lattal, 2020) (Williams et al, 2019). Given that other studies have shown that BNST neurons exhibit experience-and NMDA-receptor-dependent plasticity (Vyas et al, 2003;Dumont et al, 2005;Kash et al, 2008aKash et al, , 2008bKash et al, , 2009McElligott et al, 2010;Conrad et al, 2011;Wills et al, 2012;Haufler et al, 2013;Daldrup et al, 2016;Glangetas et al, 2017;Bjorni et al, 2020;Salimando et al, 2020), our data suggest that NMDA receptor-dependent plasticity in the BNST is critical to encoding CSs that poorly predict US onset.…”
Section: Discussionsupporting
confidence: 89%